Measuring the international spreading of the knowledge produced by French dental master theses. (24th September 2012) - Gillet, D.; Bérard, A.; Faivre, O.; Sarrazy, B.
Abstract: We estimated the international spreading of the knowledge produced by French dental master theses by searching for corresponding publications, either as articles in Medline‐indexed journals or abstracts of IADR meetings published in the Journal of Dental Research. From the 634 theses defended in 2010 in the 16 French odontology faculties, we found only one article, in a journal without impact factor, and six abstracts, over a 3‐year period (2009—2011). This corresponds to a spreading rate of 0.6%. The participation rate of French odontology faculties at IADR meetings varies from 37.5% to 81.3% depending on the year. Although there are very few studies available on the matter, it appears that this international spreading rate is much lower than both the one found by Nieminen for odontology in Finland (8.2%) and typical spreading rates of medical theses (from 6% to 41% depending on the country). This great discrepancy could be explained by the lack of specific training provided to the students; the low awareness and little engagement of the students themselves, usually more concerned with their own private practice work; and the inadequate involvement of their supervisors. To tackle the lack of appropriate training, we suggest that a specific course on scientific writing should be offered to the students in the last year of their dental master studies.